Achelous De Haan 1833 - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
Genus Achelous De Haan, 1833 Type species. Portunus spinimanus Latreille, 1819 [Type locality: Brazil]. Remarks. It is possible to narrow down the type locality of Portunus spinimanus to Brazil based on Latreille’s (1819: 47) statement in the original description “Cette espèce se trouve dans les mers de l’Amérique; elle est commune sur les côtes du Brésil ”. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 51, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155